Two new Mesenchytraeus species (Annelida: Clitellata: Enchytraeidae) from Changbai Mountain, China - Zhang, Junqian; Lu, Yajing; Xie, Zhicai (Zootaxa, 2018)
The Changbai Mountain in northeast China harbours a species-rich enchytraeid fauna, and ca. 50 species of 11 genera have been reported so far from its well-preserved ecosystems. Herein, we add two new species of Mesenchytraeus into this enchytraeid list. Both members belong to the lineage of Mesenchytraeus with enlarged ventral chaetae. Mesenchytraeus spermatoglomeratus sp. nov. is characterized by the presence of enlarged chaetae in V–VI and XI (2 per bundle), five pairs of preclitellar nephridia (VI/VII–X/XI), sperm sacs containing curly ball-shaped sperm bundles, spermathecae without diverticula, atrium with 4–6 developed prostate glands and long vasa deferentia backward to XV–XXII. Mesenchytraeus liberothecus sp. nov. is diagnosed by the presence of enlarged chaetae in V–VI (2 per bundle), five pairs of preclitellar nephridia (VI/VII–X/XI), asymmetrical paired sperm sacs containing flame-shaped sperm bundles, spermathecae with two small diverticula but free from oesophagus, atrium with 4–5 large prostate glands and short vasa deterentia confined to XI and XII. The major differences between the new species and their congeners are discussed. We also add them into the key of this enlarged chaetae lineage.